2013
DOI: 10.1002/jhm.2021
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive quality of discharge summaries at an academic medical center

Abstract: Background Discharge summaries are essential to safe transitions from hospital to home. Objective To conduct a comprehensive quality assessment of discharge summaries. Design Prospective cohort study. Subjects 377 patients discharged home after hospitalization for acute coronary syndrome, heart failure or pneumonia. Measures Discharge summaries were assessed for timeliness of dictation, transmission of the summary to appropriate outpatient clinicians and presence of key content, including elements requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 32 publications
6
83
1
1
Order By: Relevance
“…4,9,16 -18 Previous studies have shown that many physician trainees feel unprepared to write discharge summaries 13 , and that academic medical centers may trail other practice settings in the timely provision of complete summaries. 1,16 The relatively small number of responses within the academic practice subgroup (n ϭ 40) limits our ability to draw strong conclusions; however, the finding that PCPs in academic settings tend to be slightly less likely to have the HDS available at posthospital followup (when adjusted for direct access to inpatient data) offers some validation that this issue lingers. Although our survey did not address potential causative factors, differential utilization of electronic medical records in academic centers, conflicting priorities for learners and teachers (ie, not viewing documentation preparation as a learning experience) and time pressure (resulting from duty hour limitations and other educational commitments) may contribute to this result.…”
Section: Discussionmentioning
confidence: 98%
“…4,9,16 -18 Previous studies have shown that many physician trainees feel unprepared to write discharge summaries 13 , and that academic medical centers may trail other practice settings in the timely provision of complete summaries. 1,16 The relatively small number of responses within the academic practice subgroup (n ϭ 40) limits our ability to draw strong conclusions; however, the finding that PCPs in academic settings tend to be slightly less likely to have the HDS available at posthospital followup (when adjusted for direct access to inpatient data) offers some validation that this issue lingers. Although our survey did not address potential causative factors, differential utilization of electronic medical records in academic centers, conflicting priorities for learners and teachers (ie, not viewing documentation preparation as a learning experience) and time pressure (resulting from duty hour limitations and other educational commitments) may contribute to this result.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are no such reviews on DS. A timely DS seems to be associated with a reduction in hospital readmission as an indirect marker of patients' health outcome [64,73]. Improving the quality of DS helps to avoid errors and increase the quality of care, which is especially important with regard to medication errors [23].…”
Section: General Communication Aspectsmentioning
confidence: 99%
“…Moreover, large numbers of minority-serving and safety-net hospitals have low rates of rehospitalization [5, 23]. Controversy also exists within the epidemiologic literature as to whether specific discharge and transitional care practices such as patient discharge education [24], early outpatient follow-up [25-27], and improved communication between hospital and outpatient provider [28, 29] are associated with lower readmission, possibly because the quality of education, communication, and follow-up visits have been difficult to model [30]. Isolated studies have shown that higher readmission rates are associated with lower hospital case volume, lack of availability of advanced cardiac services, and lower nurse-to-patient ratios [31, 32].…”
Section: Risk Predictionmentioning
confidence: 99%